Strategic Assessment of Indonesian Furniture Industry - Ziraga, Tedo Esmu; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract. Indonesian furniture industry is known to be one of the most respective industry within Indonesia. Michael Porter introduce the theory of Diamond Model of a country competitiveness that includes 4 different aspects, which are firms structure, demand condition, supporting industry, and factor condition. Through This research author analyze the current industry condition of Indonesian furniture industry combined with the stakeholder analysis in order to determine the industry’s stakeholders. The research has an objective to give clear figure of the current industry conditions and steps that recommended in order to develop the current industry. The research is held in cooperation that involve 8 interviews with furniture companies from different sub-sectors with the validation methods of triangulation to draw the repetitive results from correspondents. The result of this research reveals Indonesian furniture industry is still lack behind in several points. The home demand condition that currently growing with the low interest of home-made products combined with the international brand penetration, decreased the internationalization power of Indonesian market. The findings urge the Indonesian furniture industry to develop its’ business process to be more adaptive and responsive to market and strengthen the current domestic market.